Effect of Salicylic Acid and Silver Nitrate on Taxol Production in Taxus baccata - G Asghari; A Mostajeran; H Sadeghi; A Nakhai (Institue of Medicinal Plants, ACECR, 2012)
Background: Taxol is an effective anticancer drug used widely in the treatment of a variety of cancers, including carcinomas of the ovary and breast. Taxol was originally isolated from the bark of Pacific yew tree Taxus bervifolia L.. Increasing demand for taxol and resource paucity of Pacific yew trees has driven several research groups to advance the taxol production methodologies, including using elicitors in suspension cultures of Taxus spp. cells. Elicitors are often used to improve taxol production incultured cells.   Objectives: The aim of this work is to inject the Taxus baccata tree a single and combination of salaicylic acid and silver nitrate to improve taxol production.   Methods: Salicylic acid and silver nitrate solution in different concentration were prepared and injected to tree. After 30 days of elicitors' injection the leave for aerial parts of the tree was collected. The dried powder of the leave was extracted by maceration with ethanol 96%. To detect taxol, a high-performance liquid chromatography (HPLC) system was employed.   Results: The treated cells with salaicylic acid and silver nitrate displayed a significant decrease in taxol. Increasing concentration of elicitors resulted lower content of taxol. Conclusion: The injection of single and combine of salaicylic acid and silver nitrate on the Taxus baccata tree showed negative effect on taxol production. It seems that more researchs need to be done in order to understand the acting mechanisms of used elicitors.